2001
DOI: 10.1081/ja-100106963
|View full text |Cite
|
Sign up to set email alerts
|

Social Context and “Natural Recovery”: The Role of Social Capital in the Resolution of Drug-Associated Problems

Abstract: This paper explores the social context of "natural recovery" from problems associated with the misuse of intoxicants. Using data collected from in-depth interviews with 46 former alcohol- and drug-dependent persons, this paper examines how the social capital that these respondents had accumulated prior to their addiction and maintained during it aided in their recovery without treatment. We specifically explore how the relations within their lives and the actual and virtual resources available to subjects thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
217
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 358 publications
(233 citation statements)
references
References 22 publications
13
217
0
3
Order By: Relevance
“…Among adults, drug cessation is a particularly critical area in the study of drug use transitions (Bruneau et al, 2004), in part due to the high mortality and morbidity associated with drug use (Hser et al, 2001). Prior research on social factors and drug cessation has tended to focus on individuals seeking treatment, yet the majority of individuals who use drugs quit without treatment (Granfield and Cloud, 2001). Furthermore, out-of-treatment samples have been found to have higher rates of HIV, risk behaviors, stimulant use, and are also older and more often non-white (Flynn et al, 1993;Watkins et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Among adults, drug cessation is a particularly critical area in the study of drug use transitions (Bruneau et al, 2004), in part due to the high mortality and morbidity associated with drug use (Hser et al, 2001). Prior research on social factors and drug cessation has tended to focus on individuals seeking treatment, yet the majority of individuals who use drugs quit without treatment (Granfield and Cloud, 2001). Furthermore, out-of-treatment samples have been found to have higher rates of HIV, risk behaviors, stimulant use, and are also older and more often non-white (Flynn et al, 1993;Watkins et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Research among African-American women in rural Florida indicates that local social support networks may moderate the negative effects of addiction (Brown and Trujillo 2003), and protective effects have also been attributed to social networks among urban Latino adolescents confronting drug use opportunities (Marsiglia, Miles, Dustman and Sills 2002). Likewise, Granfield and Cloud (2001) found that pre-existing social capital was a valuable resource for middle-class individuals recovering from addiction. However, qualitative research among smokers in disadvantaged communities in Glasgow found that social networks and social stressors combined to reinforce smoking patterns, not reduce them (Stead et al 2001).…”
Section: Content Composition and Contextmentioning
confidence: 99%
“…Such resources are broadly known as recovery capital (Cloud & Granfield, 2008). Recovery capital includes variables such as spirituality, religion, life meaning, and 12-step affiliation (Laudet, Morgen, & White, 2006) which are thought to reflect an individual's embeddedness in their social and cultural life (Granfield & Cloud, 2001;Laudet, et al, 2006). Enhancing components of recovery capital may buffer the effects of stress (Laudet, et al, 2006;Laudet & White, 2008) and lead to improved mental health.…”
Section: Study Implicationsmentioning
confidence: 99%